2018
DOI: 10.2217/cer-2017-0080
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and costs of cardiac device infections: retrospective analysis using German health claims data

Abstract: Aim: Estimate incidence and costs of cardiac device infections (CDIs) in Germany. Materials & methods:Patients had an implantable cardioverter defibrillator implanted over 2010-2013 and were followed to December 2014 using German health insurance claims data. A case-controlled analysis was performed using propensity score matching methods. Results: Risk of CDI 12 months post-implant was 3.4% overall, either 2.9% for de novo procedures versus 4.4% for replacement procedures. Mean 3-year incremental expenditure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
(30 reference statements)
2
26
0
2
Order By: Relevance
“…The prospective nature of a registry or a survey raises the awareness of the problem and increases compliance with the preventative strategy, as observed in the PADIT trial, where a trend to decreasing infections in both arms was observed during the study . A similar effect may be hypothesized by comparing the infection rate of the prospective DECODE registry (1.2%) to the retrospective studies by Ludwig et al (3.4%) and by Clémenty et al (2.3% in the ICD/CRTD cohort) in similar populations over 2010 to 2015 . Thus, it seems that physician training and compliance with a strict prevention protocol under a continued surveillance program may lower CIED infections at 1% to 1.2% nowadays .…”
Section: How To Put the Wrap‐it Data In The Broad Context Of Cied Surmentioning
confidence: 76%
See 3 more Smart Citations
“…The prospective nature of a registry or a survey raises the awareness of the problem and increases compliance with the preventative strategy, as observed in the PADIT trial, where a trend to decreasing infections in both arms was observed during the study . A similar effect may be hypothesized by comparing the infection rate of the prospective DECODE registry (1.2%) to the retrospective studies by Ludwig et al (3.4%) and by Clémenty et al (2.3% in the ICD/CRTD cohort) in similar populations over 2010 to 2015 . Thus, it seems that physician training and compliance with a strict prevention protocol under a continued surveillance program may lower CIED infections at 1% to 1.2% nowadays .…”
Section: How To Put the Wrap‐it Data In The Broad Context Of Cied Surmentioning
confidence: 76%
“…Several retrospective registries have tried to capture the infection rate across different populations of CIED recipients, yielding conflicting results that are mainly based on selection process (consecutive vs nonconsecutive patients enrollment), patients profile (age and comorbidities increased in the past 15 years), and procedure complexity (CRTD approaching 50% of high‐power devices nowadays, underrepresented in the past). Overall, infection seems to range from 1% to 4%, being associated with patient‐related factors, procedure‐related factors, and center/operator volume . Thus, the proportion of CRTD recipients, upgrades, CIED revision, patient profile, center characteristics makes a comparison of different studies unreliable.…”
Section: How To Put the Wrap‐it Data In The Broad Context Of Cied Surmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac implantable electronic device (CIED) infections are associated with a high mortality rate and high treatment costs …”
Section: Introductionmentioning
confidence: 99%